2018
DOI: 10.3390/polym10030333
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Fabrication of Polyurethane/Regenerated Silk Fibroin Composite Fibres with Tubuliform Silk-Like Flat Stress–Strain Behaviour

Abstract: Tubuliform silk is one of the seven different types of spider silks, which is well known for its unique tensile behaviour with Flat Tensile Stress-Strain (FTSS) curve. It is found that anisotropic microstructure of β-sheets is responsible for this property. In recent years, bioinspired approaches to engineer fibres supported by modern manufacturing systems have been attracting considerable interest. The present paper aims to investigate a strategy to biomimic the FTSS behaviour of tubuliform silk in synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…However, if biomimetic spinning processes are desired, the required solubility could be achieved by one or several of the following strategies. First, recent results have shown that mini spidroins containing both terminal domains and a short repetitive region can efficiently be expressed in Escherichia coli and are extraordinarily soluble (50% w/v). , Introducing Ala to Val or Ile substitutions in these proteins could therefore be afforded and still result in soluble target proteins. The mechanical properties of fibers spun from these proteins could match or even outperform those of native silk due to increased intermolecular interactions in the β-crystals.…”
Section: Optimizing the Crystal-forming Segments In The Absence Of Bi...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, if biomimetic spinning processes are desired, the required solubility could be achieved by one or several of the following strategies. First, recent results have shown that mini spidroins containing both terminal domains and a short repetitive region can efficiently be expressed in Escherichia coli and are extraordinarily soluble (50% w/v). , Introducing Ala to Val or Ile substitutions in these proteins could therefore be afforded and still result in soluble target proteins. The mechanical properties of fibers spun from these proteins could match or even outperform those of native silk due to increased intermolecular interactions in the β-crystals.…”
Section: Optimizing the Crystal-forming Segments In The Absence Of Bi...mentioning
confidence: 99%
“…below) . Expression and purification of spidroins under benign conditions, as well as subsequent biomimetic spinning protocols, have been developed and shown to recapitulate important events of the assembly process. However, the mechanical properties of fibers produced in this manner are still inferior to those of the native silk fiber, likely due to the small size of the spidroins used; hence, there is a need for novel ideas on how to produce high-performance spider silk replicas using biotechnological tools.…”
Section: Introductionmentioning
confidence: 99%
“…This is because as the amount of SnO 2 cluster increases, it interferes with the interaction of the PU polymer chains and the orientation of the PU polymer in the matrix, thus weakening the tensile strength and strain of the PU−SnO 2 composite microtube. 29 To render the PU−SnO 2 composite microtubes hydrophobic, a self-assembled monolayer (SAM) of (1H,1H,2H,2Hheptadecafluorodec-1-yl)phosphonic acid (HDF-PA), which contains a phosphoric acid anchor group, was formed on them. HDF-PA molecules bind strongly to the microtubes through interfacial bonding based on a condensation reaction between their phosphonate groups and SnO 2 on the microtube surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As the SnO 2 content in the microtube increased, the strength and strain values of the PU–SnO 2 composite microtube decreased gradually (strengths of 4.13, 3.00, 2.89, 2.93, 2.54, 2.21, and 1.85 mN tex –1 , respectively, and strains of 466.19, 356.63, 351.39, 350.57, 285.67, 211.05, and 157.92%, respectively, were determined for Microtube 1, Microtube 2, Microtube 3, Microtube 4, Microtube 5, Microtube 6, and Microtube 7). This is because as the amount of SnO 2 cluster increases, it interferes with the interaction of the PU polymer chains and the orientation of the PU polymer in the matrix, thus weakening the tensile strength and strain of the PU–SnO 2 composite microtube …”
Section: Resultsmentioning
confidence: 99%
“…Shape fixity enables acquisition of a temporary, deformed shape via a suitable programming process, whereas shape recovery retrieves the original shape via controlled application of a stimulus. 912 This shape controllability (i.e., fixity or recovery) is currently at the forefront of multiple research domains spanning biomedical, 1317 textiles, 1820 aerospace, 21,22 etc. Primarily in biomedical, SMP are attractive in critical applications including sutures, 23 stents, 24 embolic biomedical devices, 25 drug delivery devices, 26,27 tissue scaffolds, 28,29 and compression stockings.…”
Section: Introductionmentioning
confidence: 99%